If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+66=8x-6
We move all terms to the left:
4x+66-(8x-6)=0
We get rid of parentheses
4x-8x+6+66=0
We add all the numbers together, and all the variables
-4x+72=0
We move all terms containing x to the left, all other terms to the right
-4x=-72
x=-72/-4
x=+18
| x/(0.002-x)^2=0 | | 4(2x-3)=5(3x+2) | | 2^x-2=18 | | 10x+24=885x-24 | | 99x=31.9 | | -12+2x=60 | | 6x-3=9+5x | | 15/4x=7 | | (4c-5)=(2c+7) | | 5/x-4=10/x+7 | | 8x^2-26=0 | | 4a-6a-2-1=0 | | 4a-6a-2-1a=0 | | -2x+4=2(4x-3)-3(-8+5x) | | 4(6x-20)=20 | | 5+x-(14)=x-(7) | | (5+x)-14=x-7 | | 5x-4+5x=-8+10x+4 | | 4x-0.8=40 | | 2x+104=130 | | 1/3y+1=1/4 | | 3x+5-x=43 | | 3x-10=43 | | 3x-9=43 | | 2(3a+4)-3(4a-3)=2a-1 | | 4*3x+4=748 | | 2(4d+0.5)=25 | | 4z=12-8 | | 5*y/5=y | | 5*(y/5)=5y/25 | | 2.9x=162 | | 10^3-x=1 |